Impact of Intensive Insulin Stabilisation Service in Pregnancy with Type 1 Diabetes - Stephanie Teasdale; Natasha Cannon; Alison Griffin; Janelle Nisbet; H. David McIntyre (Reproductive Medicine)
Background/Objectives: Adverse pregnancy outcomes correlate with blood glucose levels in women with type 1 diabetes (T1DM). There is a gap between the glycaemic targets and the blood glucose control achieved in pregnancy. This study aimed to investigate the impact of an intensive weekly service on glycaemic control compared with our previous care model in pregnancies affected by T1DM. Materials and Methods: This is a retrospective cross-sectional pre/post study comparing measures of glycaemic control in women with T1DM in each trimester of pregnancy in the 12 months before and the 8 months after the commencement of an intensive weekly insulin stabilisation service (ISS). Results: This study utilised data from Dexcom continuous glucose monitoring (CGM) reports to analyse pregnancy-specific glycaemic data (incorporating time in the range of 3.5–7.8 mmol/L). In total, 16 women provided data for 35 trimesters pre-ISS and 17 women provided data for 38 trimesters post-ISS. There was an improvement in pregnancy-specific time in range in trimester 3 following the commencement of the intensive weekly insulin stabilisation service (pre-ISS mean: 49.6%, post-ISS mean: 61.4%, p = 0.042). Similar results were seen when women using hybrid closed-loop technology were excluded, although statistical significance was not reached. It was not possible to assess the effect of the intervention during the first trimester. There were no statistically significant changes in glycaemia in trimester 2. Conclusions: In a small group of pregnant women with T1DM, a clinically significant improvement in pregnancy-specific time in range occurred in trimester 3, but not in trimester 1 or 2, following the introduction of intensive weekly clinical support.